2022
DOI: 10.3389/fpls.2022.897027
|View full text |Cite
|
Sign up to set email alerts
|

Exogenously Applied Proline Enhances Morph-Physiological Responses and Yield of Drought-Stressed Maize Plants Grown Under Different Irrigation Systems

Abstract: The exogenous application of osmoprotectants [e.g., proline (Pro)] is an important approach for alleviating the adverse effects of abiotic stresses on plants. Field trials were conducted during the summers of 2017 and 2018 to determine the effects of deficit irrigation and exogenous application of Pro on the productivity, morph-physiological responses, and yield of maize grown under two irrigation systems [surface irrigation (SI) and drip irrigation (DI)]. Three deficit irrigation levels (I100, I85, and I70, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…A greater accumulation of proline suggested the inactivation of proline degradation under water stress [75]. After rewatering, the proline content decreased in all the watermelon accessions, suggesting that proline plays a role in osmotic adjustment and structural protection [76]. In support of the findings of our study, [77] reported that the application of exogenous proline maintained the turgidity of stressed barley and wheat plants, indicating that proline plays a role in osmotic balance.…”
Section: Discussionsupporting
confidence: 86%
“…A greater accumulation of proline suggested the inactivation of proline degradation under water stress [75]. After rewatering, the proline content decreased in all the watermelon accessions, suggesting that proline plays a role in osmotic adjustment and structural protection [76]. In support of the findings of our study, [77] reported that the application of exogenous proline maintained the turgidity of stressed barley and wheat plants, indicating that proline plays a role in osmotic balance.…”
Section: Discussionsupporting
confidence: 86%
“…Endogenous level of proline accumulation is enhanced in maize root upon low water potential, which has been reported to be a tolerance mechanism against the osmotic stress ( Kang et al., 2022 ). Besides, exogenously applied proline in maize plants can enhance the antioxidant activity, better growth performance, and prevent water loss upon osmotic stresses induced by drought and salinity ( Mosaad et al., 2020 ; Ibrahim et al., 2022 ). Polyethylene glycol (PEG)-mediated elevation of osmotic potential inhibits apical shoot growth while increasing lateral root formation, suggesting a potential mechanism of maize plants to combat water deficiency ( Ji et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous biotic and abiotic factors that affect many plants [1][2][3], such as rice [4], maize [5], and wheat [6]. Wheat (Triticum aestivum L.) is one of the most important crops in Egypt and throughout the world [7].…”
Section: Introductionmentioning
confidence: 99%